The toxicity of fumonisin B1on some biochemical and immunological parameters and its detoxification by red cabbage and garlic - Al-Fayyadh, Mohanad S.; Abdul Wadood, Shatha (Iraqi Journal of Science, 2021)
The protective effects of red cabbage and garlic extracts against liver, kidney and thyroid gland damage induced by fumonisin B1 (FB1) in male mice were studied. Sixty mice divided in to six groups. Group one are the healthy mice, Group two are mice that received a daily oral dose of only FB-1 (100 µg/kg.b.w) for 1 month, Group three: are mice that received red cabbage extract (500 mg/kg.bw) plus FB1, Group four: are mice that received red cabbage extracts, Group five: are mice that received garlic extract (500mg/kg.bw) plus FB1, group 6:are mice that received only garlic extract. After finishing the experiments, samples of blood were used for biochemical examination. The results indicated that group (2) mice treated with fumonisin B1 had significantly increased levels of immunoglobulins (IgG and IgM), kidney function parameters (urea and creatinine), proteins (albumin and total protein (TP)), and thyroid hormones (T3 and T4), along with significantly decreased level of TSH (p < 0.05). In the LD50 experiment, we are choose concentration (100 µg/kg.b.w) gavage to the mice. Oral administration red cabbage garlic extracts produced significantl reduction the levels serum IgG, IgM, T3, T4, urea, creatinine, TP and albumin and with a significant increase in TSH.